Immunohistochemical study of Wnt5a expression in cutaneous and oral lichen planus - Rania A.R Eltatawy; Ghada F.R Hassan; Asmaa M.A Qandeel; Dareen A Mohammed (Wolters Kluwer Medknow Publications, 2019)
Background Lichen planus (LP) is an inflammatory disease that affects the skin, mucous membranes, and skin appendages. Although the exact cause of LP is unclear, it was thought to be a T cell-mediated autoimmune disease. Wnt5a is one of the most extensively studied Wnt proteins, which has an important role in stimulating inflammation, cellular proliferation, differentiation, apoptosis, migration, and polarity. Objective To study the immunohistochemical expression of Wnt5a in patients with cutaneous and oral LP in comparison with healthy participants to study its possible role in the pathogenesis of the disease. Patients and methods Sixty patients with cutaneous and oral LP were included in this study, in addition to 40 healthy skin and oral mucosa specimens serving as controls. Punch biopsies of 3 mm were taken from lesional skin and control skin and were immunohistochemically stained for Wnt5a expression. Results There was a statistically significant increase in Wnt5a expression in cutaneous and oral LP lesions compared with normal controls. Moreover, Wnt5a expression was increased in hypertrophic and oral types of LP when compared with other types: classic, atrophic, and actinic. Moreover, a statistically higher expression of Wnt5a was found in hepatitis C antibodies-positive patients when compared with hepatitis C antibodies-negative patients. Conclusion Expression of Wnt5a was significantly increased in patients with LP than in controls, and this supports that Wnt5a might be involved in the pathogenesis of LP. Overexpression of Wnt5a in hypertrophic and oral types of lichen may predispose to malignant transformation. Therefore, these patients should be followed up regularly.